Views and experiences of compassion in Sri Lankan students: An exploratory qualitative study - Kariyawasam, L; Ononaiye, M; Irons, C; Stopa, L; Kirby, SE (Public Library of Science, 2021)
Practicing compassion has shown to reduce distress and increase emotional well-being in clinical and non-clinical populations. The existing research is primarily focused on Western populations although the concepts of compassion are heavily influenced by Asian Buddhist views. There is a dearth of compassion research conducted particularly in the Asian context. Therefore, this study aimed to explore the views and lived experiences of compassion in Sri Lankan students, to understand whether compassion is a socially embraced construct in Sri Lanka, considering that Sri Lanka is a Buddhist influenced society. Participants’ views and lived experiences of compassion towards themselves and to/from others were also investigated, with a specific focus on their perceived inhibitors and facilitators of compassion. Aims were set to identify whether Western compassion-based practices could be successfully applied to Asian societies such as Sri Lanka. An Interpretative Phenomenological Analysis approach was used to obtain and analyse qualitative data from a convenience sample of 10 Sri Lankan students, recruited from a Psychology course. The phenomenological analysis of the semi-structured face-to-face interviews elicited three predominant themes: What compassion means to me, what I make of it, and compassion through facilitators and inhibitors. The findings suggested that participants shared a similar understanding of the concept of compassion as reflected in the Western definitions. Experiences and views of compassion were shaped by several factors including religion, culture, society, and upbringing. In general, this study revealed that participants were well aware of the concept of compassion as well as its impact on their psychological well-being. Despite this, inhibitors existed in experiencing compassion. The religious and collectivistic-cultural influences need to be further explored and taken into account when implementing Western compassion-based practices to non-Western contexts such as Sri Lanka.